Kebiasaan Minum Jamu Kunyit Asem Atasi Nyeri Menstruasi Pada Remaja - Pratitis, Mera Putri; Firmansyah, Gunawan; Rahmawaty, Annis; Griyaningtyas, Adinda Ema; Anjarsari, Arlita Reni; Zaskia, Faricha Najwa; Al Fariza, Ismi; Auza’I, Lazuardi Zidan; Sulistyani, Linda Ayu (Jurnal Muria Pengabdian Masyarakat, 2024)
Jamu Kunyit Asam is a traditional Indonesian drink made from turmeric and tamarind. The combination of turmeric, which is famous for its curcumin content, and tamarind, which is rich in important minerals such as magnesium, makes the herbal medicine turmeric tamarind have many health benefits, such as reducing menstrual pain. This activity aims to raise awareness among young women about the use of herbal medicine turmeric as an alternative to overcome menstrual pain and introduce herbal products. The sample for this activity was 32 students from SMK Al Islam Kudus. The result of this activity is an increase in students interest in getting girls used to consuming herbal medicine and increasing their competence and skills in using tamarind turmeric. In conclusion, there is a positive response to an increase in the habit of drinking jamu kunyit asam and softskill among students